2018
DOI: 10.1002/anie.201806931
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Synthesis of Spirocyclic β‐Lactams through Copper‐Catalyzed Kinugasa/Michael Domino Reactions

Abstract: The first copper-catalyzed highly chemo-, regio-, diastereo-, and enantioselective Kinugasa/Michael domino reaction for the desymmetrization of prochiral cyclohexadienones is described. In the presence of a chiral copper catalyst, alkyne-tethered cyclohexadienones couple with nitrones to generate the chiral spirocyclic lactams with excellent stereoselectivity (up to 97 % ee, >20:1 dr). The new method provides direct access to versatile highly functionalized spirocyclic β-lactams possessing four contiguous ster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(27 citation statements)
references
References 86 publications
0
27
0
Order By: Relevance
“…In 1995, the first catalytic reaction of terminal alkynes and nitrones was developd by Miura et al [9b] . Recently, the asymmetric catalytic Kinugasa reaction was realized by the Fu group and others, and provides a catalytic enantioselective synthesis of β‐lactams from readily available starting materials [9c–j] . However these reactions can only produce a 3,4‐disubstituted product ( K ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1995, the first catalytic reaction of terminal alkynes and nitrones was developd by Miura et al [9b] . Recently, the asymmetric catalytic Kinugasa reaction was realized by the Fu group and others, and provides a catalytic enantioselective synthesis of β‐lactams from readily available starting materials [9c–j] . However these reactions can only produce a 3,4‐disubstituted product ( K ).…”
Section: Methodsmentioning
confidence: 99%
“…Very recently, Enders et al. developed an intermolecualr Kinugasa reaction followed by intramolecular desymmetric Michael addition, providing spiro polycyclic β‐lactams [9j] . The complete three‐component intermolecular sequence involving the Kinugasa reaction has not been reported to date.…”
Section: Methodsmentioning
confidence: 99%
“…In the same year, an asymmetric synthesis of spirocyclic lactams 169 was reported by Enders and co-workers using copper catalysis. 49 Indeed, cyclohexadienones 167 reacted with nitrones 168 in the presence of Cu(OTf) 2 and chiral bisoxazoline ligand 166 as the catalyst system to give domino products 169 in high enantioselectivities (82-97% ee), good diastereoselectivities (72 to >90% de) and moderate to excellent yields (55-94%) through consecutive Kinugasa and Michael reactions (Scheme 46).…”
Section: Special Topic Synthesismentioning
confidence: 99%
“…Thus, plenty of works have been focused on the exploration of Cu-based catalysts, including the synthesis method, the modification of catalytic performance and so on [24]. As for synthetic strategies, the wildly used methods are ion exchange [26], wet impregnation [27], and deposition precipitation [7,8,10] and so on, which are mainly belonged to aqueous precursor solutions methods. For example, Wang have prepared Cu/TiO2 catalysts by deposition-precipitation with urea (DPu), and found that DPu time has a great effect on the structure of TiO2 supported Cu species, e.g., Cu2(OH)3NO3 and CuO for DPu of 3 and 20 h, and results in a T100% at 75 and 90 °C, respectively, under a constant Cu loading.…”
Section: Introductionmentioning
confidence: 99%